A Simulated Prospective Evaluation of a Deep Learning Model for Real-Time Prediction of Clinical Deterioration Among Ward Patients*. Issue 8 (August 2021) - Shah, Parth K.; Ginestra, Jennifer C.; Ungar, Lyle H.; Junker, Paul; Rohrbach, Jeff I.; Fishman, Neil O.; Weissman, Gary E.
Abstract : OBJECTIVES: The National Early Warning Score, Modified Early Warning Score, and quick Sepsis-related Organ Failure Assessment can predict clinical deterioration. These scores exhibit only moderate performance and are often evaluated using aggregated measures over time. A simulated prospective validation strategy that assesses multiple predictions per patient-day would provide the best pragmatic evaluation. We developed a deep recurrent neural network deterioration model and conducted a simulated prospective evaluation. DESIGN: Retrospective cohort study. SETTING: Four hospitals in Pennsylvania. PATIENTS: Inpatient adults discharged between July 1, 2017, and June 30, 2019. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We trained a deep recurrent neural network and logistic regression model using data from electronic health records to predict hourly the 24-hour composite outcome of transfer to ICU or death. We analyzed 146, 446 hospitalizations with 16.75 million patient-hours. The hourly event rate was 1.6% (12, 842 transfers or deaths, corresponding to 260, 295 patient-hours within the predictive horizon). On a hold-out dataset, the deep recurrent neural network achieved an area under the precision-recall curve of 0.042 (95% CI, 0.04–0.043), comparable with logistic regression model (0.043; 95% CI 0.041 to 0.045), and outperformed National Early Warning Score (0.034; 95% CI, 0.032–0.035), Modified Early Warning Score (0.028; 95% CI, 0.027– 0.03), and quick Sepsis-related Organ Failure Assessment (0.021; 95% CI, 0.021–0.022). For a fixed sensitivity of 50%, the deep recurrent neural network achieved a positive predictive value of 3.4% (95% CI, 3.4–3.5) and outperformed logistic regression model (3.1%; 95% CI 3.1–3.2), National Early Warning Score (2.0%; 95% CI, 2.0–2.0), Modified Early Warning Score (1.5%; 95% CI, 1.5–1.5), and quick Sepsis-related Organ Failure Assessment (1.5%; 95% CI, 1.5–1.5). CONCLUSIONS: Commonly used early warning scores for clinical decompensation, along with a logistic regression model and a deep recurrent neural network model, show very poor performance characteristics when assessed using a simulated prospective validation. None of these models may be suitable for real-time deployment. Abstract : Supplemental Digital Content is available in the text.